Utilization of Eggshell Waste as Solid Catalyst for Biodiesel Production from Jatropha Curcas Oil - Iqmil, Hamdan (2013)
Increasing demand on the energy consumption due to modernization of the world where the major part of that energy is derived from fossil such as petroleum and natural gas where the energy-based fossil fuel has become limited resources that has drawn many researchers to look for alternative fuel which can be produced from renewable feedstock. Based on the recently research, Jatropha curcas oil that is derived from non-edible oil has a potential for biodiesel production. Eggshell has been investigated to utilize the composition of calcium carbonate as a heterogeneous catalyst for biodiesel synthesis. The objective for the experiment is by utilizing the eggshell waste as solid catalyst for biodiesel production from Jathropa curcas oil by the variation of temperature, methanol oil ratio and reaction time. The eggshell is prepared by the process of calcinations to get the calcium dioxide from the calcium carbonate. Fatty acid will be reduced to less than 1% before transesterification process by using acid catalyst of 1wt% of H2SO4, 600C, 3 hours of reaction time and 60% methanol to oil ratio. After that the process of transesterification for producing biodiesel from the refined Jatropha oil will be done in the batch reactor. There were several parameters that need to be considered which were; (1) reaction temperature (35°C, 45°C, 55°C, 60°C, 65°C), (2) methanol/oil ratio (1:1, 3:1, 5:1, 7:1, 9:1), (3) reaction time of 1h, 3h, 4h, 5h, 6h, The highest biodesel was found at 88.50% by the methanol oil ratio of 5:1, temperature of 60 0C reaction time for 5 hours.